Sustainable Power Generation through Dual-Axis Solar Tracking for Off Grid 100Wp Photovoltaic Systems - Widjanarko; Alia, Nila; Fengky Adie Perdana; Pondi Udianto; Puspitasari, Etik (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
This study investigates the development and implementation of a dual-axis solar tracking system for off-grid 100Wp photovoltaic (PV) systems to enhance energy harvesting efficiency and ensure sustainable power generation. The research addresses the limitations of fixed-tilt PV systems, which often underperform due to suboptimal solar alignment, especially in regions with dynamic weather conditions. The results demonstrated a significant increase in energy output, achieving up to 13,75% higher efficiency compared to static systems under similar operational conditions. This improvement is attributed to the system's ability to maintain optimal solar panel orientation throughout the day, facilitated by an advanced tracking algorithm and real-time sensor integration. The distinctive features of the developed system include its cost-effective design, adaptability to various geographical locations, and robust performance under fluctuating environmental conditions. The findings suggest that the dual-axis tracking system is wellsuited for deployment in remote or off-grid areas where reliable and efficient power generation is critical. Practical applications of this system are particularly relevant for rural electrification, agricultural irrigation systems, and other decentralized energy solutions in regions with abundant solar resources.